Clinical study on the use of cervilaxin as an accelerator of labor - Stabile, Américo (2015)
Our communication is to present a way of previous note a limited number of carefully selected, on the use of Cervilaxin Birnberg following the technique as a new method for accelerating delivery clinical observations. Their results syndicates it as a biological resource of real practical use as an auxiliary promising for proper handling and delivery care.